Çelişik Duygulu Cinsiyetçilik ile Flört Şiddetine Yönelik Tutum Arasındaki İlişki - Tire, Olcay; Yeşiltepe, Akgün (Fırat University, 2023)
The aim of this study is to investigate the relationship between attitudes towards dating violence and conflicting sexist attitudes. This descriptive cross-sectional study was conducted using a total of 283 students at the Faculty of Letters of Munzur University in Türkiye between February and June 2021. The data were collected using a descriptive information form, the Ambivalent Sexism Inventory and the Dating Violence Questionnaire, and analyzed using Mann Whitney U and Kruskal Wallis tests, Spearman’s correlation analysis and Bonferroni test. A statistically significant moderately positive relationship was found between the students’ attitudes of ambivalent sexism and dating violence. The students had a high level of ambivalent sexism and a low level of dating violence. In the study, it was determined that men (74.93±22.41) exhibit higher ambivalent sexism attitudes than women (60.14±22.02), and the mean dating violence rate of men (1.56±0.38) is higher than that of women (1.30±0.29). As a result of the analysis, it was determined that the hostile and protective sexist attitude, which is the sub-dimensions of ambivalent sexism, is higher in male students than in female students. Finally, it was found that those with high protective sexism attitudes have more dating violence attitudes than those with high hostile sexism attitudes. The findings reveal that the ambivalent sexist attitude supports dating violence.

The aim of this study is to investigate the relationship between attitudes towards dating violence and conflicting sexist attitudes. This descriptive cross-sectional study was conducted using a total of 283 students at the Faculty of Letters of Munzur University in Türkiye between February and June 2021. The data were collected using a descriptive information form, the Ambivalent Sexism Inventory and the Dating Violence Questionnaire, and analyzed using Mann Whitney U and Kruskal Wallis tests, Spearman’s correlation analysis and Bonferroni test. A statistically significant moderately positive relationship was found between the students’ attitudes of ambivalent sexism and dating violence. The students had a high level of ambivalent sexism and a low level of dating violence. In the study, it was determined that men (74.93±22.41) exhibit higher ambivalent sexism attitudes than women (60.14±22.02), and the mean dating violence rate of men (1.56±0.38) is higher than that of women (1.30±0.29). As a result of the analysis, it was determined that the hostile and protective sexist attitude, which is the sub-dimensions of ambivalent sexism, is higher in male students than in female students. Finally, it was found that those with high protective sexism attitudes have more dating violence attitudes than those with high hostile sexism attitudes. The findings reveal that the ambivalent sexist attitude supports dating violence.
EXAMINING THE RELATIONSHIP BETWEEN ATTITUDES OF AMBIVALENT SEXISM AND DATING VIOLENCE
Keywords: Social and Humanities Education (Excluding Economics; Business and Management); Sosyal ve Beşeri Bilimler Eğitimi (Ekonomi; İşletme ve Yönetim Hariç)